Impact of technological innovations on customer experience, profitability and financial soundness with reference to Insurance Company (Journal of Informatics Education and Research, 2025)
With rise of advance technologies in every industry, the insurance companies adapted new technologies referred as Insurtech to smoothen their services in every aspect from customer point of view and from employees’ point of view. This paper aims in discussing the technology used by insurance Companies specifically Bajaj Allianz General Insurance Company Limited and the various initiatives the company has taken in the form of digital applications for the benefit of customers, employees, management and farmers and how it has impacted the growth of the company. The paper also studies the impact of technological innovations on customer experience and profitability of the company. An attempt is made to study the financial soundness of the company with the help of CARAMELS approach. The study concludes that technological innovations have positive impact on customer experience, profitability and financial soundness of the company.